The Validity and Reliability of the Persian Version of the Xerostomia Inventory Questionnaire - Maedeh Barkhordari Dashtkhaki; Shahla Kakoei; Mohammad Hasan Larizadeh; Amir Hossein Nekouei (Shiraz University of Medical Sciences, 2024)
Statement of the Problem: Reduced saliva production or changes in the quality of saliva are major causes of xerostomia as a perceptual disease.Purpose: This study aimed to measure validity and reliability of the Persian version of the xerostomia inventory (XI) questionnaire.Materials and Method: This cross-sectional study was performed in Kerman in 2021. The sample size for this study was 100 people. To test the discriminant validity of XI, 50 healthy people (control group) and 50 people undergoing or recovering from laryngeal radiation (xerostomia group) were chosen. Cronbach's alpha coefficient was used to determine internal consistency, and the intra-cluster correlation (ICC) coefficient was used to determine test-retest reliability after two weeks. To evaluate the concurrent validity, the relationship between the total score of the questionnaire and the golden question, which was defined as "How often do you have dry mouth?" was measured.Results: Cronbach's alpha and ICC coefficient for the total XI score were 0.84 and 0.95, respectively. The mean ages of patients in the radiotherapy group and the healthy participants were 59±7.5 and 41.1±6.6 years, respectively. Participants who were having or had had laryngeal radiotherapy had a significantly higher mean total XI score than healthy individuals (p< 0.001).Conclusion: The Persian version of the Xerostomia Inventory is a valid and reliable tool for assessing xerostomia.